Our anaesthesia experiences and methods in burn patients - Bilge Tuncer; Ali Emre Akgun; Ugur Kilinc; Muge Cakirca; Merve Akin (Medicine Science)
The objective of this study was to retrospectively evaluate the anaesthesia experiences of burn patients admitted to the Ankara Bilkent City Hospital Burn Treatment Centre between 2019 and 2021. The study also aimed to identify the types of anaesthesia applied to these patients. After obtaining the approval of the Ethics Committee (E2-23-5042), the demographic data of the patients, percentage and degree of burn, aetiology of burn injury, number of surgical procedures performed and the types of anaesthesia administered, were evaluated through a retrospective review of the patient files. A total of 421 out of 462 inpatients underwent surgery under anaesthesia at least once. A total of 1,430 surgical procedures were conducted under anaesthesia in 421 patients. Sedoanalgesia was performed in 67.9% of cases, general anaesthesia in 29.8%, and regional anaesthesia in 2.3%. Anaesthetists bear a significant responsibility for the care of burn patients during surgical and intensive care procedures. It is imperative that anaesthetists are aware of the pharmacokinetic and pharmacodynamic changes that occur in burn patients, in order that they may determine the appropriate doses of the most suitable agents. In the context of multidisciplinary burn patient treatment, anaesthesiologists play a pivotal role in communication and collaboration with other members of the surgical and intensive care teams, thereby significantly impacting patient outcomes. [Med-Science 2024; 13(4.000): 957-61]